Fuzzy-TOPSIS based optimal handover decision-making algorithm for fifth-generation of mobile communications system - Liu, Qianyu; Kwong, Chiew-Foong; Zhang, Sibo; Li, Lincan (Engineering and Technology Publishing, 2019)
With the increasing demand for higher bandwidth and data rate of the mobile user. There are massive Base Stations (BS) will be deployed in the future wireless environment. Several issues could be raised dues to dense deployment of BSs, i.e. handover (HO) ping-pong effect, unnecessary HO and frequent HO. To avoid these effects, the handover decision-making strategies become extremely important to select the optimal BS among all detected BS and ensure QoS for each mobile user. In this paper, the author develops a fuzzy-TOPSIS based HO algorithm to minimise the ping-pong effect and number of HO. The proposed algorithm integrates both advantages of fuzzy logic and TOPSIS. The Received Signal Strength Intensity (RSSI) and Signal to Noise Ratio (SNR) are considered as HO criteria in this approach. For the simulation result, the proposed HO algorithm can reduce ping-pong rate and a number of HO effectivity by comparing to conventional RSSI-based HO approach and classical Multi-Attribute Decision Making (MADM) HO method, i.e. simple additive weighting (SAW) and TOPSIS.